2011
DOI: 10.1039/c1cc12746b
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed near-infrared in vivo imaging complementarily using quantum dots and upconverting NaYF4:Yb3+,Tm3+ nanoparticles

Abstract: A new multiplexed NIR in vivo imaging is showcased by using quantum dots and NaYF(4):Yb(3+),Tm(3+) nanoparticles. The 'temporal' multiplexing is demonstrated by alternating the excitation wavelengths and unmixing the emissions of different probes. Multiplexed cellular imaging and the cellular trafficking in animal models are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…A new multiplexed NIR in vivo imaging has also recently been shown by using NIR QDs and NaYF 4 :Yb 3+ /Tm 3+ nanoparticles. 225 Instead of utilizing the emitting dye to produce additional UC color, the emission bands of UC can also be selectively quenched to produce varied color outputs via utilizing the strong absorption of unremitting dye or nanoparticles. For example, Wolfbeis et al reported tuning of dual UC emission from either the NaYF 4 :Yb 3+ /Er 3+ or the NaYF 4 :Yb 3+ /Tm 3+ nanoparticles for ratiometric optical encoding by introducing various amounts of amino-reactive organic dye on the UCNP surface to selectively quench an intended UC band.…”
Section: Upconversion Emission Color Tunabilitymentioning
confidence: 99%
“…A new multiplexed NIR in vivo imaging has also recently been shown by using NIR QDs and NaYF 4 :Yb 3+ /Tm 3+ nanoparticles. 225 Instead of utilizing the emitting dye to produce additional UC color, the emission bands of UC can also be selectively quenched to produce varied color outputs via utilizing the strong absorption of unremitting dye or nanoparticles. For example, Wolfbeis et al reported tuning of dual UC emission from either the NaYF 4 :Yb 3+ /Er 3+ or the NaYF 4 :Yb 3+ /Tm 3+ nanoparticles for ratiometric optical encoding by introducing various amounts of amino-reactive organic dye on the UCNP surface to selectively quench an intended UC band.…”
Section: Upconversion Emission Color Tunabilitymentioning
confidence: 99%
“…To surmount this obstacle, an appealing alternative has emerged for using NIR light based on lanthanide doped upconverting nanoparticles (UCNPs) [119,120]. UCNPs absorb NIR light and convert it to higher-energy photons in the UV, visible, and NIR regions.…”
Section: Controllable Release Of Loaded Speciesmentioning
confidence: 99%
“…In the work of Liu group,118 they reported that PEGylated UCNPs physically loaded with organic dyes via hydrophobic force could showed tuned visible emission spectra owing to the FRET from UCNPs to the organic dyes under NIR excitation, and thus could be serve as a FRET nanosystem for in vivo multicolor UCL imaging ( Figure ). Additionally, Kim et al170 have recently demonstrated multiplexed imaging complementarily using QDs and NaYF 4 :Yb/Tm NPs by alternating the excitation wavelengths and unmixing the emissions of different probes.…”
Section: Applications Of Upconversion Nanoparticles For In Vivo Bimentioning
confidence: 99%